2021
DOI: 10.22158/elsr.v2n3p63
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perspectives on Research Collaborations between the U.S. and Mexico

Abstract: The transfer of knowledge in science, technology, engineering, and mathematics (STEM) across countries is a common practice in academia, which is both timely and useful to achieve research collaborations. Through a qualitative research approach, using interviews and observations, five STEM Mexican professors shared their experiences and expectations in leading the research collaborations where professors and students participated. This qualitative inquiry utilized Sargent and Water’s (2004) academic research c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…As shown in Figure 4, it can be found that the wireless network covers a very large area in the entire city, almost everything is covered [17]. e development of computer technology and network technology is stable and rapid, and various industries have also applied this technology.…”
Section: Evaluation Indicators Of Scientific Research Of Collegementioning
confidence: 99%
“…As shown in Figure 4, it can be found that the wireless network covers a very large area in the entire city, almost everything is covered [17]. e development of computer technology and network technology is stable and rapid, and various industries have also applied this technology.…”
Section: Evaluation Indicators Of Scientific Research Of Collegementioning
confidence: 99%